ANALISIS DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAN PEMUSTAKA DI UPT PERPUSTAKAAN UNIVERSITAS NEGERI MALANG - Mas'ud, Ali; Kresnani, Enlik (Arthavidya Jurnal Ilmiah Ekonomi, 2017)
This research is a survey of studies using research type description (explanatory research). The sample used was 100 people respondents from user in library of the State University of Malang. The sample in this study is taken by using the propational method of stratified random sampling in order to balance the sample from each stratum was adequate. The samples were taken on the basis of the proportion of student visits to library of the State University of Malang during the past year i.e., 2014.The results showed that: (1) there is a significant influence in partial dimensions between the quality of service (direct evidence, reliability, responsiveness, assurance, and empathy) towards the satisfaction of user is quite good although there is still some respondents who provide answer “less well”. (2) There are significant effects simultaneously between the dimensions of service quality (direct evidence, reliability, responsiveness, assurance, and empathy) against user satisfaction. (3) the fact that the direct evidence of the variables (X 1) do not have the greatest influence towards the satisfaction of user (Y) contribute the largest or dominant service quality dimensions (X) which has the greatest influence user satisfaction (Y) is the variable dimensions of empathy (X 5). Followed by the dimension of responsiveness (X 3) and followed by the dimension of the guarantee (X 4) as well as the dimension of reliability (X 2).